MRI Characteristics at a Mean of Thirteen Years After Lumbar Disc Herniation Surgery in Adolescents: A Case-Control Study. Issue 4 (October 2021) - Lagerbäck, Tobias; Kastrati, Gránit; Möller, Hans; Jensen, Karin; Skorpil, Mikael; Gerdhem, Paul
Abstract : Background: The purpose of this study was to describe the prevalence of lumbar spine degeneration in adult individuals who had undergone lumbar disc herniation surgery during adolescence. Methods: Twenty-three individuals who had been surgically treated for lumbar disc herniation as adolescents (⩽18 years of age) participated in this study at a mean of 13.8 years (range, 8.6 to 20.4 years) after the surgery; they were matched for age and sex to 23 controls without any known previous disc herniation or spinal surgery. Magnetic resonance imaging included sagittal T1-weighted, T2-weighted, and short tau inversion recovery (STIR) sequences of the lumbar spine. Disc degeneration was assessed with the Pfirrmann grading system. Changes in the vertebral end plate and body were assessed according to Modic changes and total end plate (TEP) score. Patient-reported outcome measures included the Oswestry Disability Index, a visual analog scale (VAS) for leg and back pain, the EuroQol-5 Dimension-3 Level (EQ-5D-3L) questionnaire, and the mental and physical component summary scores of the Short Form (SF)-36. Statistical analyses were made with the chi-square test and the Welch-Satterthwaite t test. Results: Compared with the controls, the cases that underwent surgery had a higher prevalence of the following: severe degeneration according to the Pfirrmann grading system at the L4-L5 (p = 0.007) and L5-S1 (p = 0.002) levels, Modic changes at the L4-L5 (p = 0.022) and L5-S1 (p = 0.026) levels, and a TEP score of ≥6 at the L5-S1 level (p = 0.001). The surgical cases had a significantly worse patient-reported outcome compared with the controls (all p ⩽ 0.010), with the exception of the VAS for leg pain (p = 0.093) and the mental component summary score of the SF-36 (p = 0.844). Conclusions: Lumbar disc herniation surgery that was performed during adolescence was associated with more frequent lumbar spine degeneration and lower health-related quality of life in adulthood when compared with the control group. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.